What’s in a Name? Student Pharmacists’ Novel Extracurricular Process of Drug Therapy Reinforcement - Kenric B. Ware (Journal of Education and Learning (EduLearn), 2017)
Fostering excitement in pharmacy student learning can be achieved through reinforcing drug therapies in curricular and extracurricular endeavors. This paper described an extracurricular initiative that elevated awareness of drug therapy in its current, future, and past members. This process occurred on an annual basis. Upon invitation, participants were expected to attend meetings with current and graduate organizational members. These settings provided opportunities for recognition and remembrance of organizational history and drug therapies. Checkpoints were inserted to verify progression towards full membership. The primary role of graduate members in this process was the yielding of their professional insights. A student – led, peer – facilitated model of drug therapy exposure along these lines resonates with calls for increased innovative learning strategies.